Enforcement Measures Relating to Straddling Stocks - An International and South African Perspective - Diemont, Marius (Department of Public Law, 2021)
On 10 March 1995, Canadian fisheries authorities boarded and arrested the Spanish fishing vessel, Estai, outside the Canadian 200 mile Exclusive Fishing Zone on the Grand Banks off the coast of Newfoundland alleging that the vessel was fishing in breach of the Northwest Atlantic Fisheries Organisation (NAFO) conservation and management measures. This action served to focus world attention on a dispute that had its origins in the failure of the 1982 United Nations Convention on the Law of the Sea ("the 1982 Convention") to implement an effective conservation and management regime for fish stocks on the high seas, particularly with respect to fish stocks that straddle the EEZ of Coastal states.